The Influence of Listening English Pop Songs to Improve Learners' Vocabulary at LKP Nuansa Jaya - Nurmala Hendrawaty (Loquen, 2019)
Improving English vocabulary through listening can be done by using English songs that are liked by learners. Therefore, the objectives of this research are to know whether there is an influence of listening to English songs on learners’ vocabulary at LKP Nuansa Jaya English Course in Jakarta or not and to identify and classify the word classes of six selected English pop songs. This is a quantitative and qualitative descriptive research employed by 15 young learners. There is an influence of listening English song on learners’ vocabulary at LKP Nuansa Jaya since the average score of listening test is 75.33. Dealing with identifying and classifying the word classes of six selected English song lyrics, it indicates that the most difficult word class is noun (9.51%); the second is adjective (12.08%); the third is verb (13.37%); the forth is preposition (14.14%); the fifth is adverb (15.17%); the sixth is conjunction (17.22%); the seventh or the easiest one is pronoun (18.51%). As a result, to increase learners’ vocabulary knowledge and mastery, word classes are identified chronologically in every song lyric; then, it is designed into a pocket dictionary. The selection of word classes are based on the results of learners’ vocabulary scores and familiarity. The more difficult the word classes are the more examples are provided. Besides, the meaning of the word classes is translated into Indonesian to make learners easy to understand. Keywords: Listening, English Pop Songs, Vocabulary